Incidencia del clima organizacional en el desarrollo de actividades laborales en la Universidad de Posgrado del Ecuador. Estudio de caso: IAEN, 2013-2015 - Manguia Rosero, Juan Carlos (2017)
This research analyzes the organizational climate and the relationship with the workforce development, detailed dimensions, with public rules and theory of sustenance. For effect, was taken as a case study the Instituto de Altos Estudios Nacionales, on the assumption that such factors as changes in the institutional structure, rotation of personnel and administrative management affect the organizational climate and institutional development. To test of this hypothesis, these three factors were established as the specific objectives of the research to determine how the organizational climate impacts on the development of the institution. In accordance with the objectives, we considered it necessary to carry out descriptive research, using research for documental analysis, observation and survey techniques.